Harmonic Distortion in Three-Phase Networks Using a 24-Pulse STATCOM: Modeling, Simulation, and Performance Evaluation - Mremi , Wajdi; Al-Mathnani, Ali; Alfathi, Sharaf Aldeen (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
Harmonic distortion is one of the most critical challenges affecting power quality in modern industrial networks, particularly under nonlinear loading and dynamic operating conditions. This paper presents the modelling and performance evaluation of a 24-pulse STATCOM designed to reduce total harmonic distortion (THD) in three-phase power systems. The proposed STATCOM structure is developed using four 6-pulse voltage source converters (VSCs) combined with Y–Y and Y–Δ phase-shifting transformers to achieve a 15° phase displacement, enabling natural cancellation of dominant harmonics such as the 5th and 7th orders. A detailed simulation model is implemented in MATLAB/Simulink, and system performance is evaluated under nonlinear loading conditions, including the starting of a 100-HP induction motor. The results demonstrate a significant improvement in power quality, with THD reduced to 1.52% compared to values ranging between 8–12% without compensation, alongside enhanced voltage stability at the point of common coupling (PCC) and minimized voltage sag during transient events. These findings confirm that the 24-pulse STATCOM provides an effective and economical solution for harmonic mitigation, representing a practical alternative to external filters and conventional 6- or 12-pulse compensation systems.